The Influence of Ethnicity on Students’ Self-efficacy and Self-Esteem at Sekolah Tinggi Teknologi Dumai - Julanos Julanos; Hanifatul Rahmi; Welly Desriyati; Ahmad Fauzan; Poltak Rinaldo T (Departement of Mathematics Education, 2023)
Ethnicity and culture are individual characteristics that affect the behavior of each individual. It consists of norms, beliefs, attitudes, and behaviors that incorporate into a person's self-concept. Self-efficacy and self-esteem are the behavioral aspects of how people assess their ability and consider valuable or not valuable in the family or social life. The purpose of this study was to find out, the influence of ethnicity on students' self-efficacy and self-esteem at Sekolah Tinggi Teknologi Dumai. The research was a correlational study conducted at the institution. The participant of this study was 277 students who were selected randomly from 1,054 students. This study used a set of questionnaires. The Multi Group Ethnic Identity Measure (MEIM) by Phinney, J. (1992) was adopted to measure the student's ethnicity. The General Self-efficacy Scale by Schwarzer, R., and Jerusalem, M. (1995) was adopted to measure the students' self-efficacy, and Rosenberg Self-esteem Scale by Rosenberg (1965) was adopted to measure the students' self-esteem. The finding of this study indicated that ethnicity gave a significant influence on students' self-efficacy and self-esteem at Sekolah Tinggi Teknologi Dumai.